DIGITAL FINANCIAL ACCOUNTING TRANSFORMATION IN ENHANCING THE QUALITY OF FINANCIAL REPORTING AND THE PERFORMANCE OF MSMES IN MEDAN CITY - Vina Winda Sari (RADJA PUBLIKA, 2026)
The rapid development of digital technology has transformed financial accounting practices among micro, small, and medium enterprises (MSMEs). This study examines the effect of digital financial accounting transformation on financial reporting quality and MSME performance in Medan City. A quantitative research design was employed using survey data collected from 200 MSME owners and managers who had adopted digital accounting applications in their business operations. Respondents were selected through purposive sampling, while the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital financial accounting transformation has a positive and significant effect on financial reporting quality. The use of digital accounting systems improves the accuracy, timeliness, completeness, and accessibility of financial information. Financial reporting quality also has a positive effect on MSME performance by supporting more effective financial planning, cost control, and business decision-making. Furthermore, digital financial accounting directly contributes to improved operational efficiency and business performance. These findings confirm that financial reporting quality plays an important role in strengthening the relationship between digital accounting transformation and MSME performance. The study highlights the need for MSME owners, government institutions, and business-support organizations to improve digital infrastructure, accounting literacy, and technology-based financial management capabilities.